2022
DOI: 10.5826/dpc.1203a145
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Dermatological Diseases in Geriatric Patients During Dermatology Outpatient Department Visits

Abstract: Introduction: Elderly population is vulnarable to experience a great number of dermatological diseases thanks to the intrinsic and extrinsic process of aging. Objectives: The aim of this study is to retrospectively investigate the prevalence of dermatological diseases in geriatric patients, their distribution by age and gender, and to provide a reference for studies on aging and skin problems. Methods: In the present study, patients who reported to the dermatology outpatient clinic between January 1, 2019 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, it has been investigated in patients with rosacea, with no significant difference being observed between a control group and a rosacea group [ 9 ]. A similar study involving patients with alopecia areata reported that MLR might represent a potential diagnostic marker [ 10 ]. In the present study, MLR values differed significantly between the AV patients and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been investigated in patients with rosacea, with no significant difference being observed between a control group and a rosacea group [ 9 ]. A similar study involving patients with alopecia areata reported that MLR might represent a potential diagnostic marker [ 10 ]. In the present study, MLR values differed significantly between the AV patients and the control group.…”
Section: Discussionmentioning
confidence: 99%